Development and assessment of gastric-retentive sustained release metronidazole microcapsules - Makan, Anjana (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Helicobacter pylori is one of the most common pathogenic bacterial infections and is the leading cause of gastritis, gastroduodenal ulcer disease and gastric cancers. Studies have revealed the prevalence of Helicobacter pylori is high in many countries around the globe. Although Helicobacter pylori is highly sensitive to antimicrobial agents in vitro the clinical eradication rate of the disease is still low. The instability of API at gastric pH, low concentration of API in the gastric mucosa and short gastric residence times are the main reasons for poor eradication rates. The high prevalence rate of this disease necessitates the design and development of gastric-retentive site specific oral dosage forms for the optimized delivery of existing therapeutic molecules and may be an approach to improving the eradication rate of Helicobacter pylori. Metronidazole (MTZ) is a 5-nitroimidazole derivative that exhibits antibiotic and antiprotozoal activity. MTZ is used in combination with other compounds for the treatment of Helicobacter pylori in peptic ulcer disease. MTZ is a potential candidate for inclusion in a sustained release gastric-retentive delivery system that acts in the stomach and since it is unstable in the intestinal/colonic environment enhancing gastric residence time would be a therapeutic advantage. MTZ is a cost-effective therapy that exhibits good anti-microbial activity and has a favourable pharmacokinetic profile. A sustained release gastric-retentive formulation is therefore proposed as an approach to enhance the local delivery of MTZ and improve treatment outcomes for patients infected with Helicobacter pylori. A stability indicating Reversed-Phase High Performance Liquid Chromatography (RP- HPLC) method for the quantitation of MTZ in pharmaceutical dosage forms was developed and optimised using a Central Composite Design (CCD) approach. The RP-HPLC method was found to be linear, accurate, precise, sensitive, selective, and was applied to the analysis of MTZ in commercially available medicines. Preformulation studies were conducted as preparative work prior to manufacture gastric- retentive sustained release MTZ microcapsules. The experiments conducted were tailored for the development of sustained release MTZ microcapsules using a solvent evaporation method. The particle size and shape of the microcapsules was investigated using Scanning Electron Microscopy (SEM). MTZ- excipient compatibility studies were performed using Fourier Transform Infra-red Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and X-Ray Diffraction (XRD). The results revealed that no definite interaction between MTZ and intended excipients to be used for manufacture of MTZ formulations occurred. A solvent evaporation procedure was used for the manufacture of MTZ microcapsules. Preliminary formulations were manufactured using two different grades of Methocel® at various levels. In addition the impact of processing parameters on performance was also investigated. The formulations were assessed in terms of in vitro release, buoyancy, yield, encapsulation efficiency and microcapsule size. Formulation optimisation was undertaken using a CCD approach and numerical optimisation was used to predict an optimised formulation composition that would produce minimal initial MTZ release, maximum MTZ release at 12 hours and maximum buoyancy, encapsulation efficiency and yield. The kinetics of MTZ release from microcapsules was established by fitting in vitro release data to different mathematical models. Higuchi model and first-order model appeared to best fit the data as majority of the formulation batches had highest R2 values for these models. Short-term stability assessment of the optimised formulation was established by undertaking stability studies at 25°C/60% RH and 40°C/75%RH. No significant changes in any of the CQA were observed over 30 days of stability testing. A gas chromatographic (GC) method was developed and validated for the quantitation of residual acetone and n-hexane. The optimised formulation contained 213.60 ppm/g acetone and 25.23 ppm/g n-hexane which are well below the limits set for residual solvents. In conclusion, gastric-retentive sustained release MTZ microcapsules with potential for further development and optimisation have been successfully developed and assessed in these studies.
Keywords: Metronidazole; Drug delivery systems; Helicobacter pylori; High performance liquid chromatography; Gas chromatography; Drugs; Drugs -- Controlled release